2009
DOI: 10.1007/s12185-009-0303-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of co-expression of CD21 and LFA-1 in B-cell lymphoma

Abstract: We previously reported that the prognosis of CD21-positive diffuse large B-cell lymphoma (DLBCL) is significantly favorable to that of CD21-negative DLBCL (Otsuka et al. in Br J Haematol 127:416-424, 2004). In this study, we attempted to clarify the biological significance of CD21 expression in B-cell lymphoma (BCL) by performing in vitro experiments using CD21 transfection into a CD21-negative lymphoma cell line and analyzing clinical data from lymphoma samples. Established clones of CD21 transfectants showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…CD21 encodes a membrane protein that functions as a receptor for Epstein–Barr virus (EBV) binding on B and T lymphocytes. A previous study [25] reported that the prognosis of CD21-positive DLBCL was significantly favorable to that of CD21-negative DLBCL and then a later in vivo experiment [26] showed that CD21 was closely related to LFA-1 expression in B-cell lymphoma (BCL), and the absence of CD21/LFA-1 expression was associated with pleural/peritoneal fluid involvement caused by BCL, which is a potential indicator of BCL progression. It is interesting to note that interleukin-2 receptor beta ( IL2RB ) was significant in the Cox proportional-hazards model.…”
Section: Resultsmentioning
confidence: 99%
“…CD21 encodes a membrane protein that functions as a receptor for Epstein–Barr virus (EBV) binding on B and T lymphocytes. A previous study [25] reported that the prognosis of CD21-positive DLBCL was significantly favorable to that of CD21-negative DLBCL and then a later in vivo experiment [26] showed that CD21 was closely related to LFA-1 expression in B-cell lymphoma (BCL), and the absence of CD21/LFA-1 expression was associated with pleural/peritoneal fluid involvement caused by BCL, which is a potential indicator of BCL progression. It is interesting to note that interleukin-2 receptor beta ( IL2RB ) was significant in the Cox proportional-hazards model.…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemical analyses of clinical B-cell lymphoma samples revealed CD21 expression in all evaluated cases [ 21 ]. In our study, CD21 expression was found in cells with non-dendritic morphology in the intratumoral and peritumoral areas and in the lymphocytes of the germinal center.…”
Section: Discussionmentioning
confidence: 99%
“…The LFA-1 absence prevents the leukocyte emigration to inflammation sites, resulting in a severe immunodeficiency (Drillenburg & Pals 2000;Pals et al 2007;Page et al 2012). On the other hand, previous studies have proved that LFA-1 expression provokes cell aggregation limiting its proliferation and its expression is induced by CD21 (complement receptor type 2, CR2, C3d receptor, and mature B-cell marker) (Otsuka et al 2004a;Otsuka et al 2004b;Tanimoto et al 2009;Zhao et al 2014), whose expression is lost in A20 tumour cells. This suggests that A20 B-cell lymphoma line has jointly selected the loss of CD18 and CD21 expression as tumour proliferative and development advantages, reducing the possible cell interaction and aggregation.…”
Section: Molecular and In Vitro Consequences Of The Loss Of Hvem In Amentioning
confidence: 98%